2021
DOI: 10.1186/s12916-021-02098-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of multimorbidity and changes in health-related quality of life following myocardial infarction: a UK multicentre longitudinal patient-reported outcomes study

Abstract: Background Multimorbidity is prevalent for people with myocardial infarction (MI), yet previous studies investigated single-health conditions in isolation. We identified patterns of multimorbidity in MI survivors and their associations with changes in HRQoL. Methods In this national longitudinal cohort study, we analysed data from 9566 admissions with MI from 77 National Health Service hospitals in England between 2011 and 2015. HRQoL was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…In this study, physical examination was observed in only 15.5% GP-patient consultations, while it was observed in 64.5% of GP-patient consultations in Australia ( 31 ), 79% in Estonia ( 32 ), and 72.8% in Guangzhou, China ( 17 ). Similarly, test (laboratory or imaging test) in GP-patient consultations were infrequent (17.1% consultations) in the present study, while it was recorded at 29.0% of encounters in Australia ( 29 ). This situation may be mainly due to the fact that most (84.6%) encounters in general practice clinics in the present study were revisiting to the general practice clinics.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, physical examination was observed in only 15.5% GP-patient consultations, while it was observed in 64.5% of GP-patient consultations in Australia ( 31 ), 79% in Estonia ( 32 ), and 72.8% in Guangzhou, China ( 17 ). Similarly, test (laboratory or imaging test) in GP-patient consultations were infrequent (17.1% consultations) in the present study, while it was recorded at 29.0% of encounters in Australia ( 29 ). This situation may be mainly due to the fact that most (84.6%) encounters in general practice clinics in the present study were revisiting to the general practice clinics.…”
Section: Discussionsupporting
confidence: 55%
“…Multimorbidity has been rising in prevalence over recent years. In China, 30.3% of older adults reported multimorbidity ( 28 ), while the prevalence of multimorbidity was 53.5% in UK ( 29 ), 19.5% in 45.6% in Canada ( 30 ). In China, people with multimorbidity need to visit multiple specialists if they want to receive care in hospital.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In a large national longitudinal cohort study, increasing comorbidity was associated with worsening HRQoL. 28 The large increase in the risk of death at 5 years that we show suggests that the primary focus in older adults with significant multimorbidity and NSTE-ACS should be on interventions that also provide benefits in quality of life. Given the paucity of existing evidence, there is need for randomised trials in older people with comorbidities to guide the most appropriate management strategies and allow honest, patient-centred discussions about the goals of management.…”
Section: Discussionmentioning
confidence: 79%
“…The importance of the impact of cardiac interventions on health-related quality of life (HRQoL) is being increasingly recognised in this older population—but is often reported to be poor by older adults following NSTE-ACS 27. In a large national longitudinal cohort study, increasing comorbidity was associated with worsening HRQoL 28. The large increase in the risk of death at 5 years that we show suggests that the primary focus in older adults with significant multimorbidity and NSTE-ACS should be on interventions that also provide benefits in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Due to improved survival, patients with stable chronic coronary disease post STEMI represent an increasingly important and prevalent population [2,3,4]. Non-cardiac comorbidities are frequent in patients with acute myocardial infarction (AMI) [4,5]. The presence of non-cardiac comorbidities in patients with AMI can be explained by the presence of the same risk factors for both AMI and non-cardiac comorbidity (e.g., smoking is also a risk factor for chronic obstructive pulmonary disease, peripheral artery disease, stroke, etc.…”
Section: Introductionmentioning
confidence: 99%